Assessment the effect of diabetes education on self-care behaviors and glycemic control in the Turkey Nursing Diabetes Education Evaluating Project (TURNUDEP): a multi-center study - Selda Celik; Nermin Olgun; Feride Taskin Yilmaz; Gulden Anataca; Ilksen Ozsoy; Nurcan Ciftci; Elif Fidan Aykiz; Serap Yasa; Ebru Karakiraz; Yeliz Ulker; Yeliz Erdem Demirhan; Sultan Yurtsever Celik; et al. (BMC, 2022)
Abstract Background Diabetes education in Turkey is provided by diabetes nurse educators in almost all healthcare organizations. However, the education is not standardized in terms of learning content, duration, and methods. This multi-center study was performed to assess the self-care behaviors and glycemic control following education provided to the patients with type 2 diabetes mellitus by diabetes nurse educators. Methods This was a descriptive and cross-sectional study and included 1535 patients admitted to 28 public hospitals for the treatment of type 2 diabetes mellitus. The education was assessed by using a Patient Identification Form and Self-care Scale. Results The proportion of individuals who received diabetes education within the last year was 78.5%, with 46.7% of them having received it once. Of the patients, 84.8% reported that they received diabetes education individually. It was found that the proportion of individuals who received education about oral antidiabetics (78.5%) and glucose testing at home (78.5%) was higher than the proportion of individuals who received education about exercise (58.8%) and foot care (61.6%). The status of diabetes education, education intervals, and the correlation of the education method with self-care and glycemic control was evaluated. Self-care and glycemic control levels were better among the patients who received diabetes education thrice or more and in patients who received education both individually and in a group (p < 0.05). Conclusions Approximately three-quarters of individuals with type 2 diabetes mellitus received education by diabetes nurse educators in Turkey. Diabetes education is positively correlated with self-care and glycemic control levels among patients with type 2 diabetes mellitus. Efforts for generalization and standardized education for all diabetes patients are necessary.